2022
DOI: 10.3390/jcm11020357
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Rehabilitation in the Intensive Care Unit for Patients with Severe COVID-19 Pneumonia: A Retrospective Cohort Study

Abstract: This retrospective cohort study aimed to examine the rehabilitation effect of patients with coronavirus disease 2019 (COVID-19) in the intensive care unit (ICU) under mechanical ventilation and included ICU patients from a university hospital who received rehabilitation under ventilator control until 31 May 2021. Seven patients were included, and three of them died; thus, the results of the four survivors were examined. The rehabilitation program comprised the extremity range-of-motion training and sitting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Long-term physical, cognitive and psychosocial consequences have been identified in ICU survivors from the CARDS. Several authors pleaded for the implementation of early rehabilitation in mechanically ventilated patients with CARDS [19][20][21]. Stutz et al demonstrated the feasibility of implementing physical and occupational therapy in a population of critically ill COVID-19 patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term physical, cognitive and psychosocial consequences have been identified in ICU survivors from the CARDS. Several authors pleaded for the implementation of early rehabilitation in mechanically ventilated patients with CARDS [19][20][21]. Stutz et al demonstrated the feasibility of implementing physical and occupational therapy in a population of critically ill COVID-19 patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Já nos pacientes em ventilação mecânica, apesar fraqueza adquirida na UTI, falha no desmame e disfagia pós extubação, a mobilização precoce pode ser iniciada de forma lenta e progressiva, seguindo-se protocolos de despertar e respiração e monitoramento (EGGMANN et al, 2020). A reabilitação precoce surge com potencial para os pacientes com COVID internados em UTI, reduzindo, conforme evidenciados também nos estudos acima, o tempo em ventilação mecânica, internação hospitalar, e bem como a otimização nas atividades de vida funcionais (KINOSHITA et al, 2022).…”
Section: Objetivos Da Terapiaunclassified
“…Grande parte dos casos eram representados por doença leve, cerca de 80%. Aos demais, 20% precisavam de intervenção e 5% eram internados com demandas para unidade de terapia intensiva (KINOSHITA et al, 2022).…”
unclassified
“…Furthermore, Kinoshita et al. 18 ) and Sakai et al. 19 ) demonstrated the importance of early rehabilitation therapy for patients with severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%